Dekonstruksi Altman Z-Score: Dampak Individual Rasio Keuangan Terhadap Kapitalisasi Pasar Perusahaan Transportasi dan Logistik Era Post-Pandemi - Ana Maulida; Khoirul Fatah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Post-pandemic transformation creates complexity in evaluating transportation industry financial health requiring deconstructive approaches toward conventional prediction models. This research aims to analyze individual influence of Altman Z-Score components on market capitalization of transportation and logistics companies in the post-pandemic era. Explanatory quantitative methodology was applied to 25 transportation companies listed on Indonesia Stock Exchange during 2020-2023 period, utilizing panel data regression techniques with random-effect model approach. Research findings reveal significant paradox: working capital to total assets ratio demonstrates negative influence (coefficient = -1.056; p = 0.048), contradicting theoretical expectations. Conversely, market value of equity to total liabilities ratio (coefficient = 0.196; p = 0.000) and asset utilization efficiency (coefficient = 1.388; p = 0.000) exhibit dominant positive contributions to firm valuation. Findings confirm insignificance of retained earnings and operational profitability in determining investor perception. The model explains 94.9% of market capitalization variability, indicating robustness of deconstructive analysis. Research concludes that investors prioritize operational efficiency and market confidence over traditional liquidity indicators, reflecting paradigm evolution in performance evaluation within structurally disrupted industries.